2004
DOI: 10.2460/ajvr.2004.65.592
|View full text |Cite
|
Sign up to set email alerts
|

Identification and concentration of soy phytoestrogens in commercial dog foods

Abstract: Soybean and soybean fractions are commonly used ingredients in commercial dog foods. Dietary intake of phytoestrogens may have both beneficial and deleterious health effects. Our results indicated that certain commercial dog foods contain phytoestrogens in amounts that could have biological effects when ingested long-term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…Plant material is used to extend the shelf life of dry diets and provides a necessary source of carbohydrate for the expansion and cooking processes of dry diets (Zoran 2002). Previous evaluations of the isofl avone content of companion animal diets have found a signifi cant correlation between soy and isofl avone content (Court and Freeman 2002;Cerundolo et al 2004). Our fi ndings also demonstrated a signifi cant relationship between the total content of isofl avone and the inclusion of soy.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Plant material is used to extend the shelf life of dry diets and provides a necessary source of carbohydrate for the expansion and cooking processes of dry diets (Zoran 2002). Previous evaluations of the isofl avone content of companion animal diets have found a signifi cant correlation between soy and isofl avone content (Court and Freeman 2002;Cerundolo et al 2004). Our fi ndings also demonstrated a signifi cant relationship between the total content of isofl avone and the inclusion of soy.…”
Section: Discussionsupporting
confidence: 61%
“…Over 75% of the diets evaluated were found to contain at least one of the four isofl avones investigated, which is considerably higher than the 46% of feline diets (Court and Freeman 2002) or the 57% of canine diets (Cerundolo et al 2004) reported for North America.…”
Section: Discussionmentioning
confidence: 73%
“…Diets of other animal species contain large amounts of PE such as those detected in commercial chow of cats (Setchell et al, 1987 andFreeman, 2002), dogs (Cerundolo et al, 2004) and rodents (Thigpen et al, 1999, Brown and Setchell, 2001and Degen et al, 2002 with the protein source being soy meal. These findings indicate that all investigators should be vigilant to the PE composition of laboratory animal diets because these agents might have a direct effect on the outcome of bioassays designed to detect developmental toxicity or carcinogenicity (Casanova et al, 1999, Thigpen et al, 1999and Brown and Setchell, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, both bone meal and/or soybean meal are common ingredients in commercial dog chows. (65) Normal bone maintenance in dogs has been shown time and again in diets containing 0.5% Ca. (66) Bone meal and other various by-products can provide an overabundance of Ca, and soybean meal provides unnecessarily high concentrations of phytoestrogens (65) that can influence bone metabolism.…”
Section: Dogsmentioning
confidence: 99%
“…(65) Normal bone maintenance in dogs has been shown time and again in diets containing 0.5% Ca. (66) Bone meal and other various by-products can provide an overabundance of Ca, and soybean meal provides unnecessarily high concentrations of phytoestrogens (65) that can influence bone metabolism. (67) One only has to peruse the literature related to OVX and OHX dogs that report dietary mineral contents to realize Ca concentrations are routinely excessive (>1% (26,27,(44)(45)(46)(47)(48)59,63) ) in those studies not deliberately restricting or controlling Ca intakes.…”
Section: Dogsmentioning
confidence: 99%